A perception among general dental practitioners and postgraduates of Central India toward the use of "magnifying loupes" in clinical practice - A questionnaire-based survey - Sangham Dinkar Madakwade; Chetana S Makade; Pratima Ramakrishna Shenoi; Rajesh Kubde; Himani Vilas Thawale; Vinay Harishchandra Tiwari (Wolters Kluwer Medknow Publications, 2021)
Background: The introduction of magnification aids such as dental operating microscope and magnifying loupes is one of the most important technologies that have improved dental treatment quality and allow dentists to enhance their visibility and accuracy for diagnosis and treatment. Aim: The aim of the study was to determine the awareness, attitude, and prevalence of usage of magnifying loupes among the general dental practitioners and postgraduate students in Central India. Methodology: A close-ended validated questionnaire was structured to assess the awareness, attitude, and prevalence of magnifying loupes among the general dental practitioners and postgraduate students in Central India. Data were analyzed with simple descriptive statistics (SPSS Ver 22). Results: Almost 91.9% of the participants were aware of dentistry magnification, whereas only 47.17% of the participants were using them in their clinical practice. Conclusions: Although most participants were aware of the magnifying loupes, its practical usage was limited to only 47.17%.